World Wide Warriors How Jihadis Operate Online - Lohlker, Rüdiger (2019)
The contributions of this volume aim at a new, evidence based approach to Jihadism studies. What is the structure of Jihadi online communication and the dissemination of operational material online? Which errors were made by conventional Jihadism research? Which programs, apps, etc. use Jihadis to further their online communication? Next to these questions the contributors discuss the evident inability to understand basic mathematical principles in conventional Jihadism research and consider a very important video as a case study of Jihadi online communication, stressing the linguistic and theological shortcomings of conventional research. The volume is based on the understanding of theological elements as a vital part of Jihadi communication.